Mapping continuous learning using social network research: a social network study of Australian Genomics as a Learning Health System. Issue 10 (5th October 2022) - Ellis, Louise A; Long, Janet C; Pomare, Chiara; Mahmoud, Zeyad; Lake, Rebecca; Dammery, Genevieve; Braithwaite, Jeffrey
Abstract : Objectives: To explore a macrolevel Learning Health System (LHS) and examine if an intentionally designed network can foster a collaborative learning community over time. The secondary aim was to demonstrate the application of social network research to the field of LHS. Design: Two longitudinal online questionnaires of the Australian Genomics learning community considering relationships between network members at three time points: 2016, 2018, 2019. The questionnaire included closed Likert response questions on collaborative learning patterns and open-response questions to capture general perceptions of the community. Social network data were analysed and visually constructed using Gephi V.0.9.2 software, Likert questions were analysed using SPSS, and open responses were analysed thematically using NVivo. Setting: Australian Genomic Health Alliance. Participants: Clinicians, scientists, researchers and community representatives. Results: Australian Genomics members highlighted the collaborative benefits of the network as a learning community to foster continuous learning in the ever-evolving field of clinical genomics. The learning community grew from 186 members (2016), to 384 (2018), to 439 (2019). Network density increased (2016=0.023, 2018=0.043), then decreased (2019=0.036). Key players remained consistent with potential for new members to achieve focal positions in the network. Informal learning was identified as the most influential learning method for genomic practice. Conclusions: This study shows that intentionally building a network provides a platform for continuous learning—a fundamental component for establishing an LHS. The Australian Genomics learning community shows evidence of maturity and sustainability in supporting the continuous learning culture of clinical genomics. The network provides a practical means to spread new knowledge and best practice across the entire field. We show that intentionally designed networks provide the opportunity and means for interdisciplinary learning between diverse agents over time and demonstrate the application of social network research to the LHS field.